Approach for Smart Use of Wastes and Biofuels - De Simio, Luigi; Iannaccone, Sabato (The Global Environmental Engineers, 2021)
The urgent need to reduce greenhouse gas emissions by gradually abandoning fossil fuel sources is required due to climate-changing emergencies. Employing as much as possible renewable energy, in any form and any field, together with a reduction of per capita energy need, can reduce this tendency and contrast the catastrophic consequence of our planet temperature increasing. In this scenario, biofuels production, together with reuse and recycling represent a correct strategy to contrast environmental degradation. Biofuel has been the subject of great interest over the past decade. Their development from the first to the fourth generation has led to significant improvements in the production cycles and extended the interest in new resources. The availability of different choices could permit to use always the best solution to maximize the result. In this paper, the different biofuel generations are presented with the aim of highlighting strengths and weaknesses to identify a smart approach to energy conversion and land utilization. Even today the first-generation biofuels are the most widespread, while second-generation gives a small contribution, with a low replacement share of fossil fuels. Land use and competition with other human necessities are the most relevant constraints in this evaluation. In general, the production of gaseous fuels requires less energy than liquid for both the first as well as second-generation technologies. When considering gaseous options, biomethane should be preferred for convenient energy balance in the productive process and when biogas cannot be directly employed. Moreover, biomethane gives the possibility to be added to the existing gas network. The new third and fourth-generation technologies could allow a considerable efficiency increase while reducing the problem of the biofuel productive chain.